2014
DOI: 10.1093/eurpub/cku033
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of and knowledge about tobacco use among physicians in the Odessa region, Ukraine

Abstract: We investigated prevalence of and knowledge about tobacco use among physicians, and their counselling of patients in the Odessa region (Ukraine). Paediatricians (40), family doctors (40) and interns (70) were selected from the physician population of the Odessa region. The proportion of smokers was unacceptably high for health care professionals: paediatricians, 32.5%; family doctors, 37.5%; and interns, 50%. Majority of smokers were men. Less than half of smokers had considered quitting or seriously attempted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
2
3
0
1
Order By: Relevance
“…In a study in Ukraine smoking rate was found 32.5% in pediatricians, 37.5% in family physicians (12). Our results show that an important part of physicians and nurses still smoke (27.6% and 34.4% respectively).…”
Section: Discussionsupporting
confidence: 42%
“…In a study in Ukraine smoking rate was found 32.5% in pediatricians, 37.5% in family physicians (12). Our results show that an important part of physicians and nurses still smoke (27.6% and 34.4% respectively).…”
Section: Discussionsupporting
confidence: 42%
“…Smoking has been decreasing in recent years in Europe. However, the study by Arvayeva et al assessing the prevalence of smoking among GPs in Ukraine shows a high percentage of smokers (57% among men and 15% among women) [42]. In contrast, a study of GPs in Flanders has shown that smoking is rare among doctors, as opposed to alcohol consumption [43].…”
Section: Discussionmentioning
confidence: 99%
“…Kutlu ve arkadaşlarının 2005'te Meram Tıp Fakültesi hemşireleri ile yaptığı çalışmada sigara içme sıklığı % 56,5; Uysal ve arkadaşlarının 2007'de 374 hekim ile yaptığı çalışmada %16; Yıldız ve arkadaşlarının 2010'da 773 hekim ile yaptığı çalışmada %30,2, Çalışkan ve arkadaşlarının 2005'te Ankara Tıp Fakültesi öğrencileri ve çalışanları ile yaptığı çalışmada %34,5'tir [8][9][10][11][12][13]. Pakistan'da 180 sağlık çalışanı ile yapılan çalışmada sigara içme sıklığı %29,4, Ukrayna'da yapılan bir çalışmada ise sigara içme sıklığı pediatristlerde %32,5, aile hekimlerinde %37,5 ve intörnlerde %50'dir [14][15]. Yunanistan'da 220 hemşire ile yapılan bir çalışmada ise sigara içme sıklığı %32'dir [16].…”
Section: Discussionunclassified